The problematic of identity-memory in the Cuban-American fiction of Cristina García and Achy Obejas - Fernández Jiménez, Mónica (Complutense Journal of English Studies, 2021)
In their fiction oeuvre, Cuban-American authors Cristina García and Achy Obejas demonstrate concerns related to the fragmented memory of Cuban-American second-generation migrants. The particular political status of this exile community together with the difficulty to access familial memories back in the homeland cause in the protagonists a series of conflicts affecting their sense of identity. However, as the narratives progress, these conflicts prove to be a result of the prevalence of nationalism and linearity in traditional notions of identification. Through an alternative relation with history, memory, and identity the protagonists of these works contest undisputed postulates on the study of memory such as Maurice Halbwachs’. They also reflect postcolonial theories which have challenged the influence of Western epistemology in approaching these issues and consider the changing paradigm of identification in an increasingly globalised and mobile world.